2010 Vittorio de Nora Award Winner: Designing Crushing and Grinding Circuits for Improved Energy Efficiency - Zeljka Pokrajcic (The Minerals, Metals and Materials Society, 2010)
Crushing and grinding, or comminution, circuits are the most energy intensive process of a mineral processing plant. Comminution involves the physical size reduction of an orebody to a particle size sufficient for recovery of the mineral values. However, the comminution process remains inherently inefficient. The inefficiency is a result of the operating nature of comminution devices such as grinding mills, where transfer of energy between grinding media and particles in unconstrained and completely random. New comminution circuit design strategies are presented in this paper. The aim of the new strategies is to improve the overall efficiency of the comminution process and reduce the total energy consumption of a comminution circuit. The energy efficient strategies include the: ? rejection of coarse size liberated gangue from the comminution circuit and further downstream size reduction ? use of more efficient grinding and crushing equipment ? the selection of coarser particle product sizes to alleviate the increased energy intensity required to achieve finer product sizes Singularly and when combined, these energy efficient strategies can significantly decrease the overall energy consumption of a comminution circuit. This paper also explores the financial impact of certain energy efficient strategies using an analysis tool called EcoNomics?. It shows that substantial financial gains can be made by including more efficient technologies and methods in comminution circuit design.